2009
DOI: 10.1136/hrt.2009.174557
|View full text |Cite
|
Sign up to set email alerts
|

Persistent precordial "hyperacute" T-waves signify proximal left anterior descending artery occlusion

Abstract: Persistent precordial "hyperacute" T-waves signify proximal left anterior descending artery occlusion Verouden, N.J.; Koch, K.T.; Peters, R.J.; Henriques, J.P.; Baan, J.; van der Schaaf, R.J.; Vis, M.M.; Tijssen, J.G.; Piek, J.J.; Wellens, H.J.; Wilde, A.A.; de Winter, R.J. Published in: Heart DOI:10. 1136/hrt.2009.174557 Link to publication Citation for published version (APA):Verouden, N. J., Koch, K. T., Peters, R. J., Henriques, J. P., Baan, J., van der Schaaf, R. J., ... de Winter, R. J. (2009). Persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
172
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(182 citation statements)
references
References 20 publications
2
172
1
7
Order By: Relevance
“…In most patients, a 1-to 2-mm ST-segment elevation in the lead aVR is found. This pattern was thoroughly described by de Winter et al 2,3 in 2008, and since then several cases have been reported. In most cases, the proximal segment of the left anterior descending artery was occluded.…”
Section: Response To Ecg Challengementioning
confidence: 88%
See 2 more Smart Citations
“…In most patients, a 1-to 2-mm ST-segment elevation in the lead aVR is found. This pattern was thoroughly described by de Winter et al 2,3 in 2008, and since then several cases have been reported. In most cases, the proximal segment of the left anterior descending artery was occluded.…”
Section: Response To Ecg Challengementioning
confidence: 88%
“…Some authors defend that a collateral blood supply might protect the myocardium from transmural ischemia and prevent the ST-segment elevation. However, in the article of Verouden et al, 3 in a cohort of 1890 patients with anterior ST-segment elevation myocardial infarction who were referred for primary coronary angiography and presented an occlusion of the proximal left anterior descending artery, only a few patients who also presented de Winter's pattern had Rentrop Grade 3 collateral blood supply. These authors postulated that the area of transmural ischemia was so large that no injury currents were generated toward the precordial leads but only directed upward to an aVR lead.…”
Section: Response To Ecg Challengementioning
confidence: 99%
See 1 more Smart Citation
“…This is characterized by ST depression and T wave apical and symmetrical from V1 to V5 leads, associated or not with ST elevation at AVR, denoting total occlusion of the anterior descending artery. The recognition of this electrocardiographic pattern is fundamental, since many of these patients are classified as coronary syndrome without ST elevation delaying immediate primary reperfusion [5].…”
Section: Discussionmentioning
confidence: 99%
“…3 However, if seen in patients with typical symptoms and at a relatively slow heart rate, regional ischemia due to subtotal occlusion of the LAD or left circumflex coronary artery should be suspected. 47,48 Patients presenting with such an ECG pattern often progress to typical STEMI (Fig. 4).…”
Section: The Ecg In Patients With Ongoing Typical Symptomsmentioning
confidence: 99%